The Moderating Role of Good Corporate Governance on the Influence of Company Size, Share Value, Profitability, and Financial Leverage on Income Smoothing (Study of Primary Consumer Goods Companies listed on the BEI in 2020-2022) - Pratami, Naturi Diah; Tubastuvi, Naelati; Innayah, Maulida Nurul; Aryoko, Yudhistira Pradhipta (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of company size, share value, profitability, and financial leverage on income smoothing and the moderating role of GCG on the influence of company size, share value, profitability, and financial leverage on income smoothing. This research uses quantitive method , purposive sampling, and logistic regression analysis with SPSS 20. This research shows that profitability has a negative effect on income smoothing. company size, share value, and financial leverage do not affect incomes smoothing. GCG cannot moderate the influence of company size and share value on income smoothing. GCG can strengthen the influence of profitability and financial leverage on income smoothing.